(untitled) (Revista de Ciências Agroveterinárias, 2025)
Symbiotic Culture of Bacteria and Yeasts (SCOBY) is one of the main constituents of kombucha, consisting of a bacterial film that forms on the surface of the tea. This is a material that has a favorable fiber composition and biodegradable capacity. Thus, the present study aimed to analyze the factors that influenced the development of SCOBY in order to use it as a raw material to produce new biodegradable materials. The symbiotic culture of bacteria and yeasts showed the best yield (66.8 g) in the experiment prepared with green tea, stored at 30ºC and in a container with a surface area equal to 361 cm2. The addition of bacterial cellulose to the films resulted in a material with better mechanical and thermal resistance. It was concluded that sample B1, with bacterial cellulose and a smaller amount of glycerin in its composition, would be the biofilm with the best characteristics for the production of biopackaging, considering that it has a lower moisture content, greater weight, better mechanical properties, such as greater tensile strength and a higher percentage of elongation, in addition to being a material resistant to high temperatures.